A health‐risk appraisal model and endoscopic mass screening for esophageal cancer in Japanese men. Issue 2 (27th March 2012) - Yokoyama, A.; Oda, J.; Iriguchi, Y.; Kumagai, Y.; Okamura, Y.; Matsuoka, M.; Mizukami, T.; Yokoyama, T.
SUMMARY A strong association between inactive aldehyde dehydrogenase‐2 (ALDH2) and risk of esophageal cancer has been demonstrated in East Asian drinkers. An alcohol flushing questionnaire asking about past and current tendency for facial flushing to occur after drinking a glass (≈180 mL) of beer predicts the presence of inactive ALDH2 among Japanese aged 40 years or older with a sensitivity and specificity of approximately 90%. We invented a health‐risk appraisal (HRA) model that makes it possible to identify Japanese men who are at high risk for esophageal cancer based on their past and current alcohol flushing tendency, drinking, smoking, and intake of vegetables and fruits. Between 2008 and 2009, 2221 Japanese men aged 50 years or older filled out the HRA questionnaire before undergoing a screening examination by upper gastrointestinal endoscopy at five medical facilities. The endoscopic examination resulted in a diagnosis of esophageal cancer in 19 subjects, and 117 (5.27%) subjects had an HRA score ≥11. The proportion of subjects with an HRA score ≥11 was higher in the 50–69 age group (6.11–6.88%) than in 70–89 age group (2.84–2.86%). The esophageal cancer detection rate was 4.27% among the subjects with an HRA score ≥11 and only 0.67% among the other subjects. Based on a receiver operating characteristic curve analysis, when an HRA score of ≥9 was used for subjects aged 50–69 years and of ≥8 for those aged 70–89 years as the cutoff value to select individuals with a high risk for esophageal cancer, its sensitivity and false‐positive rate was 52.6% and 15.2%, respectively, and the cancer detection rate was 2.91% in the high‐risk group, as opposed to 0.48% in the other group. In conclusion, the high detection rates for esophageal cancer in the high‐risk groups encouraged screening based on our HRA model in larger Japanese populations.